2019
DOI: 10.3390/cancers11040467
|View full text |Cite
|
Sign up to set email alerts
|

Association between Dietary Salt Intake and Progression in the Gastric Precancerous Process

Abstract: Gastric cancer is the third leading cause of cancer mortality worldwide. Studies investigating the effect of salt on gastric cancer have mainly used self-reported measures, which are not as accurate as sodium/creatinine ratios because individuals may not know the amount of salt in their food. Using data from a prospective cohort study, we investigated the effect of salt intake on progression to gastric precancerous lesions. Salt intake was estimated by urinary sodium/creatinine ratios, self-reported frequencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 55 publications
1
18
0
2
Order By: Relevance
“…In the study, H. pylori infection was not evaluated and could not be excluded as a confounding factor. Thapa et al (14) showed that salt intake estimated by urinary sodium/creatinine ratio is associated with progression of GC or dysplasia in patients with persistent H. pylori infection at a risk ratio of 1.49. This result was originally intended for patients who were positive for H. pylori, and H. pylori-uninfected patients were not included.…”
Section: Discussionmentioning
confidence: 99%
“…In the study, H. pylori infection was not evaluated and could not be excluded as a confounding factor. Thapa et al (14) showed that salt intake estimated by urinary sodium/creatinine ratio is associated with progression of GC or dysplasia in patients with persistent H. pylori infection at a risk ratio of 1.49. This result was originally intended for patients who were positive for H. pylori, and H. pylori-uninfected patients were not included.…”
Section: Discussionmentioning
confidence: 99%
“…Production of low gastric acid makes an ideal environment for some nitrogen reducing bacteria that convert nitrates or nitrites from the saliva and dietary substrates further produce carcinogenic N-nitroso compound which causes damage to DNA and methylation of epithelial cells promotes carcinogenesis of the stomach. High dietary salt intake promotes gastric carcinogenesis [85]. Epidemiological reports showed that a high intake of salt is related to the incidence of H. pylori infection.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…[85]. The two fundamental components which induce gastric cancer are Cytotoxin-Associated Gene A (CagA) and Vacuolating Cytotoxin A (VacA)[77].…”
mentioning
confidence: 99%
“…• H. pylori is present in half of world's population and its prevalence increases with age (25-60% in Europe, Muhammad, 2012); it persistently colonizes the human stomach despite a robust immune response (Algood, 2006). • Increasing evidence (Wang, X 2008;Yassibas, 2012;Epplein, 2014), including prospective studies (Shikata, 2006;Thapa, 2019), indicates that in presence of persistent colonization of H. pylori, high salt intake can exert synergistic effects in promoting gastric carcinogenesis. Considering the high prevalence of H. pylori infection in Europe, the biological relevance for the general healthy population, and the biological plausibility of the combined effect of salt intake and H. pylori (Gaddy, 2013), we consider that there is a need of further well conducted studies on this topic.…”
Section: Recommendations For Researchmentioning
confidence: 99%